Parabolic Solar Water Heater Efficiency Enhancement Using Live Sun Tracking - Bankar, Amit; Padole , Prajwal; Thakre, Jaydev; Bhure , Yogesh; Meshram , Durgesh; Kotgale , Vaibhav (International Journal on Theoretical and Applied Research in Mechanical Engineering, 2025)
This project proposes the development of a Parabolic Solar Water Heater with an automated real-time sun-tracking system to maximize solar energy absorption throughout the day. The system incorporates a parabolic reflector to focus sunlight onto a heat-absorbing pipe, efficiently heating water. To enhance efficiency, the system employs Light Dependent Resistor (LDR) sensors to detect sunlight intensity and DC motors to adjust the parabolic dish's orientation dynamically. The motors, controlled by a microcontroller, ensure optimal alignment with the sun, increasing energy absorption and overall system performance. A temperature sensor continuously monitors the water temperature and displays real-time data, enabling users to track heating efficiency. The system is designed to be energy-efficient, cost-effective, and eco-friendly, making it a viable alternative to conventional water heating methods. The incorporation of automated tracking significantly improves energy utilization compared to static solar heaters. This project aims to contribute to sustainable energy solutions by providing an efficient, renewable, and autonomous water heating system for residential and commercial applications. The proposed design ensures higher thermal efficiency, real-time monitoring, and automation, making it a promising advancement in solar thermal energy utilization.